Beyond Grief and Survival: Posttraumatic Growth Through Immediate Family Suicide Loss in South Korea. (September 2019) - Lee, Eunjin; Kim, Sung won; Enright, Robert D.
The purpose of this qualitative study was to explore the characteristics of posttraumatic growth arising from losing an immediate family member to suicide in Korea. We used interpretative phenomenological analysis for data collection and analysis and conducted in-depth interviews with 11 participants in Korea to evaluate the positive changes subsequent to the suicide. Participants revealed positive outcomes in response to losing an immediate family member to suicide after suffering the "most unimaginable pain" including (a) "Now I know what the most important thing in life is, " (b) "Warm and intimate relationships matter, " and (c) "Survivors of suicide's search for meaning." The implications of these findings and avenues for future research are discussed.